Descomposición histórica de la inflación en Perú. Distinguiendo entre choques de demanda y choques de oferta - Lavanda, Guillermo (2011)
This paper analyzes and distinguishes the role and importance of the shocks related to the aggregate demand and aggregate supply on the behavior of the Peruvian inflation during the period 1997:1-2009:2. We use the methodology based on structural vector autoregressive (SVAR) models using a long-run identification based on Blanchard and Quah (1989) which allows to obtain the historical decomposition of the annual inflation. Unlike Salas (2009), this paper uses a more simple model of aggregate demand and aggregate supply, and a larger sample. The results show that the behavior of inflation was largely explained for shocks related to the aggregate demand side in comparison with aggregate supply shocks. Furthermore, the results of the variance decomposition of the prediction error show that in the short and long term, the shocks of the demand side explain around 70% and 60% of the movements of the inflation. The results are robust to the inclusion of different variables in the set of information.